Intermuscular differences in force generation ability among biarticular hamstring muscles during the late swing phase in maximal speed sprinting - Miyazaki, T.; Fujii, N. (Sports Biomechanics, 2023)
We aimed to investigate how intermuscular muscle-tendon architectural differences among biarticular hamstring muscles (biceps femoris long head [BFlh], semimembranosus [SM] and semitendinosus [ST]) influence intermuscular differences in muscle force during the late swing phase in maximal speed sprinting. Using a musculoskeletal model, we estimated the muscle-tendon kinematics, muscle force, and force generation ability, defined by force-length-velocity properties and pennation angle, of the biarticular hamstring muscles in 40 male athletes during the late swing phase. SM force generation ability was smaller during the first half of the late swing phase and larger during the second half than the BFlh and ST. The intermuscular differences in force generation ability were caused by the intermuscular differences in time-varying muscle-tendon unit, muscle fibre and tendon lengths, which might be affected by the muscle-tendon architecture of this model, particularly optimal muscle fibre length, tendon slack length and insertion location. Moreover, the peak muscle force was achieved earlier in the BFlh and ST than in the SM. These findings suggest that intermuscular differences in muscle-tendon architecture among the biarticular hamstring muscles can induce intermuscular differences in time-varying muscle force by influencing time-varying force generation ability and muscle-tendon kinematics during the late swing phase.